2016
DOI: 10.1002/mrc.4480
|View full text |Cite
|
Sign up to set email alerts
|

13C dynamic nuclear polarization using isotopically enriched 4‐oxo‐TEMPO free radicals

Abstract: The nitroxide-based free radical 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) is a widely used polarizing agent in NMR signal amplification via dissolution dynamic nuclear polarization (DNP). In this study, we have thoroughly investigated the effects of N and/or H isotopic labeling of 4-oxo-TEMPO free radical on C DNP of 3 M [1- C] sodium acetate samples in 1 : 1 v/v glycerol : water at 3.35 T and 1.2 K. Four variants of this free radical were used for C DNP: 4-oxo-TEMPO, 4-oxo-TEMPO- N, 4-oxo-TEMPO-d and 4-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Another method that may be adopted is the use of scavengers such as sodium ascorbate during the dissolution process to reduce nitroxide free radicals such as 4-oxo-TEMPO can prolong the hyperpolarization lifetime of nuclear spins. [43] Other ways that may further boost the DNP enhancement levels or expedite the polarization transfer process include 1 H-13 C cross polarization, [27,44,45] microwave frequency modulation during DNP irradiation, [46] appropriate choice of free radicals, [47][48][49][50] lanthanide doping, [16,29,38,51] 13 C enrichment, [52] and deuteration [53] of the glassing matrix in the DNP sample. Finally, we would like note that the total cost of the commercial parts and machined pieces of our homebuilt hyperpolarizer system, with the exclusion of the cost of the widebore superconducting magnet and dedicated NMR spectrometer, is only slightly under USD95,000.00-a small fraction of the cost of the commercial HyperSense polarizer (Oxford Instruments, UK) and the clinical SpinLab hyperpolarizer (GE Healthcare, WI).…”
Section: Resultsmentioning
confidence: 98%
“…Another method that may be adopted is the use of scavengers such as sodium ascorbate during the dissolution process to reduce nitroxide free radicals such as 4-oxo-TEMPO can prolong the hyperpolarization lifetime of nuclear spins. [43] Other ways that may further boost the DNP enhancement levels or expedite the polarization transfer process include 1 H-13 C cross polarization, [27,44,45] microwave frequency modulation during DNP irradiation, [46] appropriate choice of free radicals, [47][48][49][50] lanthanide doping, [16,29,38,51] 13 C enrichment, [52] and deuteration [53] of the glassing matrix in the DNP sample. Finally, we would like note that the total cost of the commercial parts and machined pieces of our homebuilt hyperpolarizer system, with the exclusion of the cost of the widebore superconducting magnet and dedicated NMR spectrometer, is only slightly under USD95,000.00-a small fraction of the cost of the commercial HyperSense polarizer (Oxford Instruments, UK) and the clinical SpinLab hyperpolarizer (GE Healthcare, WI).…”
Section: Resultsmentioning
confidence: 98%
“…17,18,20,21,31,34,49 Trityl OX063, the stable organic radical used in this work, has a very narrow EPR linewidth that makes it ideal for polarizing low-γ nuclei such as 13 C. When using this free radical to polarize low-γ nuclei such as 13 C spins, DNP data at 3.35 T and temperatures close to 1 K have shown indications of thermal mixing (TM) as the predominant DNP mechanism. 24,[50][51][52][53] Other DNP data at similar conditions suggested that the mechanism could be a combination of the solid effect (SE) and cross effect (CE).…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29][30] Additionally, the DNP efficiency of these radicals may be increased through other means such as deuteration of the glassing matrix. [31][32][33] Meanwhile, the trityls, particularly OX063, which have some of the narrowest EPR linewidths among free radicals, were found to be excellent polarizing agents for low-γ nuclei like 13 C. 16,34 When using these radicals, DNP enhancements may be improved further by the addition of trace amounts of gadolinium. [34][35][36][37] Recently, it was found that the addition of holmium to a trityl-doped sample results in liquid state enhancement similar to that achieved by using gadolinium.…”
Section: Introductionmentioning
confidence: 99%
“…1419 Furthermore, certain sample preparation methods such as the addition of trace amounts of lanthanides in the DNP sample can significantly boost the DNP-enhanced NMR signals. 5,2023 Previous studies have shown that 13 C enrichment 24 and deuteration 17,21,25 of the glassing matrix can expedite and also improve the DNP enhancement levels, respectively. All of these DNP sample optimization practices so far were additives or certain isotopic enrichment in the glassing matrix.…”
Section: Introductionmentioning
confidence: 99%